'From a woman's point of view': the Presbyterian archive as a source for women's and gender history in eighteenth- and nineteenth-century Ireland. Issue 170 (November 2022) - Calvert, Leanne
Abstract: This article responds to 'An agenda for women's history in Ireland, 1500–1900' by highlighting the explanatory potential of the Presbyterian archive in extending and reshaping our understanding of women, gender and the family in Ireland. Discussed here as the 'Presbyterian archive', the records of the Presbyterian church offer a tantalising insight into the intimate worlds of women and men in eighteenth- and nineteenth-century Ireland. Although Presbyterians were a minority religious community in Ireland, their records provide much more than a marginalised picture. Instead, the Presbyterian archive casts fresh light on the wider Irish evidence, enriching our knowledge of the everyday lives of women and men in Ireland. The article begins by introducing the Presbyterian archive and the community responsible for its creation. Next, it considers how the Presbyterian archive both meets and advances the aims of the 'Agenda' and reveals what it can tell us about the lives of women and men as gendered subjects. Overall, the article underlines the importance of the Presbyterian archive as a source for Irish historians because it underscores why all history is gender history.